Five Centuries of Civil Procedure: The Polish Experience in a European Context (16th to 21st Centuries) - Bérier, Franciszek Longchamps de,; Dziadzio, Andrzej, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
The first codification of Polish court proceedings was made in 1523. Half a millennium later, the jurists in this volume have carefully analyzed the transformation of Polish civil procedure from then to the present day against the historical background of the development of modern European legal orders and institutions. This study is the result of the work of a research group established at the Jagiellonian University in Kraków, consisting of historical and modern jurists and scholars of civil procedure and private law. Contributors are: Grzegorz J. Blicharz, Andrzej Dziadzio, Radosław Flejszar, Krzysztof Fokt, Kacper Górski, Jan Halberda, Vincent R. Johnson, Izabela Lewandowska-Malec, Martin Löhing, Franciszek Longchamps de Bérier, Dorota Malec, Maciej Mikuła, Andrzej Olaś, Grzegorz Smyk, Kamila Staudigl-Ciechowicz, and Abdoul Yatera.